KAED website updating work progress & KAED website: data entry template - Yaali, Syarel Azill; Ayob, Mohd Fairullazi (2017)
These two paper works are prepared and deliberated in Kulliyyah management meeting to update the work progress of KAED website and to provide template of data entry for KAED website.